1972
DOI: 10.1104/pp.50.5.556
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-induced Changes in Avena Coleoptile Cell Wall Composition

Abstract: Sugar and uronic acid residues were derived from wall polysaccharides of oat (Avena sativa, var. Victory) coleoptiles by means of 2 N trifluoroacetic acid, 72% sulfuric acid, or enzymic hydrolysis. The products of hydrolysis were reduced and acetylated to form alditol acetates which were analyzed using gas chromatography. Time-course studies of auxin-promoted changes in Wiegand and Schrank (31). Seeds were dehulled, placed in distilled water at room temperature for 4 hr, then spread on the surface of distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
93
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 23 publications
12
93
0
Order By: Relevance
“…59, 1977 thesis of secondary wall cellulose. Callose is apparently mobilized as a reserve material in pollen (48), and there are other reports in the literature which implicate turnover of noncellulosic glucans of cell walls (14,23,31,34). Callose has also been observed to be deposited behind the tip of growing pollen tubes (18), and it has been suggested that it serves to strengthen the tube wall (48), although the possibility that it turns over has apparently not been explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59, 1977 thesis of secondary wall cellulose. Callose is apparently mobilized as a reserve material in pollen (48), and there are other reports in the literature which implicate turnover of noncellulosic glucans of cell walls (14,23,31,34). Callose has also been observed to be deposited behind the tip of growing pollen tubes (18), and it has been suggested that it serves to strengthen the tube wall (48), although the possibility that it turns over has apparently not been explored.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent data of Klis (25) indicate that when hydroxyproline content is expressed as per cent of the dry weight of cell wall, its content continually increases during cell elongation, but that there is no further increase once the cells have obtained their final length. Also of interest are studies -showing that a specific decrease in noncellulosic glucose, which is accompanied by a roughly compensating increase in cellulose, occurs in the cell wall of Avena coleoptiles elongating in response to auxin in the absence of an external carbon source (31,39), and it has been suggested that changes in noncellulosic wall glucan may be involved in wall loosening (34). cultured in vitro in a synthetic medium supplied with IAA and GA3 (10).…”
Section: Supported By Energy Research and Development Administrationmentioning
confidence: 99%
“…Of those wall components that constitute Poaceae cell walls, the (1--3),(1l-4)-f-D-glucans are the prominent polysaccharides undergoing auxin-induced changes. Glucan metabolism has been observed during auxininduced elongation of Avena (16,23), Hordeum (24), Zea (12), and Oryza (26) coleoptiles. Two enzymes, an endo-and an exoglucanase, are involved in the hydrolysis of the polysaccharide in maize (Zea mays L.) coleoptiles (2,9,10).…”
mentioning
confidence: 99%
“…Auxin accelerates the loss of f3-D-glucan from walls of excised coleoptile tisues deprived of exogenous sugar (24), but there is no such decrease in glucan content in intact tissues during maximal growth (8) or in excised tissues given sucrose (13). Both auxin and gibberellins act in the graviresponse of the oat pulvinus (4,7,14), indicating that hormone-induced changes in f3-D-glucan content may accompany the graviresponse.…”
mentioning
confidence: 99%